Ադրբեջանի տեղեկատվական քաղաքականությունը ապրիլյան քառօրյա պատերազմում - Նազարյան, Հայկ (YSU Journal of International Affairs, 2017)
The article analyses the main directions of Azerbaijani information policy, based on mass media publications and information in social networks. Along with military operations, Azerbaijani propaganda was active in the internal audience showing that the resources it wasted for decades were not in vain: playing the external threat card, it prevented the growing discontent in the country and drew the attention of the society from Aliyevs’ offshore affairs. Azerbaijan targeted the international community in order to present Armenia as an aggressor, undermine Artsakh’s image and cause tensions in Armenia by disseminating false information. The article consists of several parts: Azerbaijani information policy in internal, international and Armenian audiences. The analysis of information flows shows that spreading disinformation, appearing as a “victim”, circulation of unfavorable information flows by biased analysts are the basic tools of the Azerbaijani propaganda.
Keywords: Artsakh, Armenian side, Azerbaijan, informational politics, propaganda, military operations, outer audience, inner audience